The Kankanaey Ritual Practices of Pamakan and Daw-es in the Context of Ecological Disaster vis-à-vis the Christian Anointing of the Sick and Rites for the Departed: A Contrapuntal Reading - Doctolero, Jaime (Animo Repository, 2003)
The study applied dialogue as an approach to the meeting of gospel and culture. It staged contrapuntal reading as a method of dialogue juxtaposing Kankanaey healing practices with Christian healing beliefs. The Kankanaey healing and Christian healing, both found out to be profoundly religious, seemed to have converged when the residents of Ucab, Itogon, Benguet performed their pamakan and daw-es rites after the onslaught of Typhoon Ompong (Mangkhut). The typhoon occasioned a landslide that left dozens of small-scale miners lifeless beneath earth and rubble. The decision of the elders and civil leaders to perform the rites began to unravel the religious worldview of the Catholic Kankanaeys. The pamakan is a ritual meal done on different occasions with the adikaila or unseen deities and spirits as necessary guests, and daw-es is a cleansing rite after burial driving away the bad or angry spirit of the dead. These two rites served as components of the healing ritual for the survivors and the community after the disaster. These rites were performed to give respect to those who perished. The study looked into the possibility that these Christian indigenous peoples did an anointing of the sick using these ritual practices. It sought if the healing ritual was compatible with or had the same function as the anointing of the sick. It was found out that elderlies, manbunongs, ministers, and church workers accompanied the disaster-struck Kankanaey communities. The accompaniment incorporated indigenous and Christian concepts and practices of healing together. The pamakan and daw-es were employed as healing rites or anointing rites. The ministry included the healing of the environment and ecology. The pamakan and daw-es were further analyzed. The rite of anointing of the sick was analyzed, too. Both indigenous and Christian rites have strengths and limitations. Both have their unique elements, too. The uniqueness or factor of the otherness of both rites is also a resource for checking and balancing what needs to be integrated or discarded. By way of contrapuntal reading, it is found out that to enrich further the Christian notion of healing among the Kankanaeys, the anointing of the sick has to take into account that pamakan induces harmony and communion, daw-es has a psychological value, indigenous healing ritual connotes a communitarian spirituality of ecology, the rites includes healing of ecology, there is a need of rites of reception for corpses during search and retrieval operations, and the community has a role in the healing process. In enriching further the Kankanaey healing belief, a punitive view of God from the indigenous consciousness must be dealt with through dialogue and catechism, a narrow notion of illness and suffering needs to be updated and broadened, and the absence of Jesus’ model of healing has to be corrected by incorporating Jesus’ style of healing. Taking into account all these factors in developing a healing rite for survivors and families after disasters among Catholic Kankanaeys is one way of enriching both the gospel and the indigenous culture.